Clostridium perfringens: a rare cause of spondylodiscitis case report and review of the literature. (3rd September 2018) - Seller, M.; Burghardt, R.D.; Rolling, T.; Hansen-Algenstaedt, N.; Schaefer, C.
Abstract: Presented is a case of a 64-year old male with a unique and yet unreported case of a spondylodiscitis caused by Clostridium perfringens. Becoming symptomatic with massive neurological deficits. Computed tomography (CT) revealed typical signs of spondylodiscitis involving the vertebral body L5 with extensive vacuum phenomenon.